Encounters with Adversity: A Framework for Understanding Resilience in Later Life - Manning, Lydia K. (Aging Ment Health, 2019)
BACKGROUND AND OBJECTIVES: We explore the internal and external resources that older adults use to negotiate adversity and related to later life. We investigated the experiences older adults had with adversity and explored the factors that promote and protect resilience and the how these factors shaped the process of managing adversity related to aging. RESEARCH DESIGN AND METHODS: Semi-structured interviews were conducted with 64 resilient adults ranging in age from 53 to 94 years of age, with an average of 71. Participants were defined as resilient on the basis of their willingness to identify as such. Grounded Theory coding techniques were applied to identify themes reflecting distinct ways in which participants dealt with what they indicated were the most significant hardships and adversities in their lives. RESULTS: What emerged from the narratives about resilience and adversity were accounts of expressions of resilience that reflected the importance in having a resilient identity. Three major themes reflecting psychological and behavioral factors were derived from the data: 1. having vital components of resilience, or behaviors and beliefs in place, that encompass resilience as a way of being; 2. a broad but articulate set of strategies that participants actively engaged with to manage adversity, and 3. a set of protective practices used to prevent risk and prevail in the face of hardship. DISCUSSION AND IMPLICATIONS: Findings suggest that dealing with adversity in later life requires the use of substantial internal and external resources in what can characterized as a proactive fashion. The results are presented as an interpretation of the participants’ perceptions of their resilience and the role it plays in self-concept, strategic planning, and proactive practices. Implications for helping to put resilience into everyday practice are considered.